The Relationship Between Family Support and Anxiety of Breast Cancer Patients undergoing Chemotherapy at Dr. H. Abdul Moeloek Hospital, Lampung Province, 2019 - Ilham Akbar; Octa Reni; H. Edy Ramdhani (International Medical Journal Corp. Ltd, 2025)
Background : According to WHO, breast cancer sufferers will increase by 20% every year and 84 million people will die worldwide. One of the treatments for breast cancer is chemotherapy. However, chemotherapy has physical and psychological side effects that will cause anxiety in patients, which will actually complicate the healing process, so family support is needed so that patients will not think that the chemotherapy they are undergoing is something threatening. Research objective: to determine the relationship between family support and anxiety in breast cancer patients undergoing chemotherapy at Abdul Moeloek Hospital, Bandar Lampung. Type of research : analytical survey, with a cross-sectional design . The population is all breast cancer patients undergoing chemotherapy at RSUD. Abdul Moeloek Bandar Lampung in 2018, totaling 120 people, and the sample uses accidental-sampling . This study uses univariate and bivariate analysis with statistical tests, namely chi square . Results: found from 120 breast cancer patients, the majority had good family support of 84.2%, and patients who were not anxious were 58.3%. The results of statistical tests with Chi Square on Pearson Chi Square p value (0.000) <0.05. Conclusion : There is a relationship between family support and anxiety in breast cancer patients undergoing chemotherapy at Abdul Moeloek Hospital, Bandar Lampung in 2018.